The next-generation DNA vaccine platforms and delivery systems: advances, challenges and prospects - Lu, Bowen; Lim, Jing Ming; Yu, Boyue; Song, Siyuan; Neeli, Praveen; Sobhani, Navid; K, Pavithra; Bonam, Srinivasa Reddy; Kurapati, Rajendra; Zheng, Junnian; Chai, Dafei (Frontiers in Immunology, 2024)
Vaccines have proven effective in the treatment and prevention of numerous diseases.However, traditional attenuated and inactivated vaccines suffer from certain drawbacks such as complex preparation, limited efficacy, potential risks and others. These limitations restrict their widespread use, especially in the face of an increasingly diverse range of diseases. With the ongoing advancements in genetic engineering vaccines, DNA vaccines have emerged as a highly promising approach in the treatment of both genetic diseases and acquired diseases. While several DNA vaccines have demonstrated substantial success in animal models of diseases, certain challenges need to be addressed before application in human subjects. The primary obstacle lies in the absence of an optimal delivery system, which significantly hampers the immunogenicity of DNA vaccines. We conduct a comprehensive analysis of the current status and limitations of DNA vaccines by focusing on both viral and non-viral DNA delivery systems, as they play crucial roles in the exploration of novel DNA vaccines. We provide an evaluation of their strengths and weaknesses based on our critical assessment. Additionally, the review summarizes the most recent advancements and breakthroughs in pre-clinical and clinical studies, highlighting the need for further clinical trials in this rapidly evolving field.